Identity and Social Pressure in The Death of Vivek Oji A Postcolonial Analysis - Houaria Chaal (PT Agung Media Publisher, 2025)
This study examines postcolonial African literature, focusing on the themes of identity and societal pressures in contemporary settings. The research is based on Akwaeke Emezi’s novel, The Death of Vivek Oji, which presents a complex portrayal of identity formation within a postcolonial society. Using a postcolonial analytical framework, this study critically explores the sociocultural values embedded in the novel and their influence on the protagonist’s life decisions. The analysis considers how postcolonial theory helps in understanding the preservation of identity amidst colonial legacies and societal constraints. The findings indicate that postcolonial societies often struggle to maintain their cultural identity due to the historical impact of colonialism, which sought to erase indigenous identities. The novel reveals that traditional values exert significant pressure on individuals, particularly those who deviate from societal norms, leading to conflicts between personal identity and collective expectations. This study highlights how postcolonial societies resist new Western ideologies out of fear of further identity transformation. The rejection of these ideas stems from a deep-rooted need to reclaim and safeguard cultural heritage. The analysis suggests that the protagonist’s struggles reflect broader societal tensions in postcolonial contexts. The study underscores the ongoing conflict between cultural preservation and modern influences in postcolonial societies, emphasizing the lasting effects of colonial legacies on identity formation.